PATIENT SAFETY IN MELANOMA SURGERY - Borges-Costa, João; de Almeida, Luís Soares; Fernandes, Isabel; Fortes, Elias; Marques, Manuel Sacramento (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Introduction: patient safety is a growing concern in healthcare management. The main objectives of our work were the detection of potentially avoidable errors in the treatment of patients with melanoma and search for solutions to improve patient safety. Material and methods: FMEA (Failure Mode and Effect Analysis) was used for analysis of the potentially avoidable errors in melanoma surgery. Results: Failure to attend surgery or post treatment follow up and wrong site surgery were the most potentially dangerous procedural errors found in melanoma treat- ment. An informatic application was used to improve communication between the laboratory and the clinician and to avoid both failures to deliver a positive result to the patient and loss of follow up. Conclusions: dermatologists, working together with other healthcare workers, must actively search for opportunities to improve patient safety du- ring melanoma treatment. KEYWORDS – Patient safety; Melanoma; Role of informatics.